2010
DOI: 10.1073/pnas.1005566107
|View full text |Cite
|
Sign up to set email alerts
|

Humanized nonobese diabetic-scid IL2rγnullmice are susceptible to lethalSalmonellaTyphi infection

Abstract: Salmonella enterica serovar Typhi, the cause of typhoid fever, is host-adapted to humans and unable to cause disease in mice. Here, we show that S.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
111
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 120 publications
(115 citation statements)
references
References 66 publications
4
111
0
Order By: Relevance
“…It is well known that the restriction against S. typhi in mice is not due to a barrier effect as mice are even resistant to intraperitoneal infection (Collins and Carter, 1978). Recent chimeric humanized mouse models demonstrate that the host restriction in bone marrow derived cells applies to systemically administered S. typhi (Firoz Mian et al, 2011;Libby et al, 2010;Song et al, 2010). Consistent with the infection experiments in culture, S. typhi did not cause infection of wild-type mice whereas the absence of TLR11 led to lethal systemic infection, even with a low dose infection (10 4 CFU per animal), with dissemination of the bacteria to different organs ( Supplementary Fig 6C,D).…”
Section: Infection Of Tlr11 Knockout Mice By S Typhi Is Dependent Onsupporting
confidence: 63%
See 1 more Smart Citation
“…It is well known that the restriction against S. typhi in mice is not due to a barrier effect as mice are even resistant to intraperitoneal infection (Collins and Carter, 1978). Recent chimeric humanized mouse models demonstrate that the host restriction in bone marrow derived cells applies to systemically administered S. typhi (Firoz Mian et al, 2011;Libby et al, 2010;Song et al, 2010). Consistent with the infection experiments in culture, S. typhi did not cause infection of wild-type mice whereas the absence of TLR11 led to lethal systemic infection, even with a low dose infection (10 4 CFU per animal), with dissemination of the bacteria to different organs ( Supplementary Fig 6C,D).…”
Section: Infection Of Tlr11 Knockout Mice By S Typhi Is Dependent Onsupporting
confidence: 63%
“…The transplantation of mice with human immune cells can render mice susceptible to S. typhi infection by intraperitoneal inoculation, suggesting that the host-specificity of S. typhi also results from a requirement for human mononuclear cells (Firoz Mian et al, 2011;Libby et al, 2010;Song et al, 2010). Our studies suggest that TLR11 is critical for preventing infection by Salmonella typhi following the normal, oral, transmission route.…”
Section: Infection Of Tlr11 Knockout Mice By S Typhi Is Dependent Onmentioning
confidence: 77%
“…T6SS variants have been acquired at least three times within the Salmonella lineage, and little is known about their function and mechanism, although most reports have implicated roles for the S. Typhimurium SPI-6 T6SS in the pathogenesis of mice and infection of macrophages (5,9,17,19,24,28,30,38). We found that the disruption of noncore T6SS clusters 2 and 4 caused significant defects in systemic dissemination in mice and that disruption of noncore gene clusters 1 and 3 resulted in a significant intracellular replication defect in macrophages.…”
Section: Discussionmentioning
confidence: 99%
“…These studies fail to mimic the essential aspects of immunity induced by S. Typhi [8]. Moreover, the determinants of host defense system to S. Typhimurium and S. Typhi are basically different [9][10][11][12] and earlier studies designate that the host immune interaction in response to S. Typhimurium and S. Typhi are qualitatively diverse.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, the determinants of host defense system to S. Typhimurium and S. Typhi are basically different [9][10][11][12] and earlier studies designate that the host immune interaction in response to S. Typhimurium and S. Typhi are qualitatively diverse. The lack of a small model has been a foremost hindrance in understanding the virulence mechanisms of S. Typhi [8]. In contrast, there are no reports available on physiological and molecular response of host altered by S. Typhi and S. Typhi Ty21a.…”
Section: Introductionmentioning
confidence: 99%